Alpinia oxyphylla Miq extract reduces cerebral infarction by downregulating JNK-mediated TLR4/T3JAM- and ASK1-related inflammatory signaling in the acute phase of transient focal cerebral ischemia in rats - Chin-Yi Cheng; Su-yin Chiang; Shung-Te Kao; Shang-Chih Huang (BMC, 2021)
Abstract Background Post-ischemic inflammation is a crucial component in stroke pathology in the early phase of cerebral ischemia-reperfusion (I/R) injury. Inflammation caused by microglia, astrocytes, and necrotic cells, produces pro-inflammatory mediators and exacerbates cerebral I/R injury. This study evaluated the effects of the Alpinia oxyphylla Miq [Yi Zhi Ren (YZR)] extract on cerebral infarction at 1 day after 90 min of transient middle cerebral artery occlusion (MCAo) and investigated the molecular mechanisms underlying the regulation of c-Jun N-terminal kinase (JNK)-mediated inflammatory cascades in the penumbral cortex. Rats were intraperitoneally injected with the YZR extract at the doses of 0.2 g/kg (YZR-0.2 g), 0.4 g/kg (YZR-0.4 g), or 0.8 g/kg (YZR-0.8 g) at MCAo onset. Results YZR-0.4 g and YZR-0.8 g treatments markedly reduced cerebral infarction, attenuated neurological deficits, and significantly downregulated the expression of phospho-apoptosis signal-regulating kinase 1 (p-ASK1)/ASK1, tumor necrosis factor receptor-associated factor 3 (TRAF3), TRAF3-interacting JNK-activating modulator (T3JAM), ionized calcium-binding adapter molecule 1 (Iba1), p-JNK/JNK, inducible nitric oxide synthase, cyclooxygenase-2, tumor necrosis factor-α, toll-like receptor 4 (TLR4), glial fibrillary acidic protein (GFAP), nuclear factor-kappa B (NF-κB), and interleukin-6 in the penumbral cortex at 1 day after reperfusion. SP600125 (SP), a selective JNK inhibitor, had the same effects. Furthermore, Iba1- and GFAP-positive cells were colocalized with TLR4, and colocalization of GFAP-positive cells was found with NF-κB in the nuclei. Conclusion YZR-0.4 g and YZR-0.8 g treatments exerted beneficial effects on cerebral ischemic injury by downregulating JNK-mediated signaling in the peri-infarct cortex. Moreover, the anti-infarction effects of YZR extract treatments were partially attributed to the downregulation of JNK-mediated TLR4/T3JAM- and ASK1-related inflammatory signaling pathways in the penumbral cortex at 1 day after reperfusion.